The relationship between teacher skills in the qualitative evaluation of math lessons with math anxiety, academic procrastination and thinking style - Tahereh Rahimi; Atefeh Sedaghat Khah (University of Hormozgan, 2022)
The current research aimed to investigate the relationship between teacher skills in qualitative evaluation of math lessons with math anxiety, academic procrastination and students' thinking style. The research was a descriptive correlational study. The statistical population was teachers and high school students of Shiraz (Iran) in 2022, from which 126 teachers and 212 students were selected by accessible sampling method. Data analysis using descriptive statistics (mean and standard deviation) and inferential (correlation and regression to examine the relationships between variables) were done by SPSS-22. The results indicated that teacher skills in qualitative evaluation had a negative relationship with math anxiety and academic procrastination, and there was also a positive relationship between teacher skills in qualitative evaluation and students' thinking styles. The regression results also showed that teachers' skills in qualitative evaluation predicted students' math anxiety and academic procrastination, significantly. According to the findings of the research, it is suggested to use effective interventions to increase the qualitative evaluation skills of teachers in order to improve the academic efficiency and academic performance of students.